Hubungan Efikasi Diri dengan Kemampuan Pemecahan Masalah Kreatif (Creative Problem-Solving) pada Pelajar - Sachiko Aqila Naila Ismail; Klarista Klarista Annora Kusumawardani; Suparmi Suparmi (Jurnal Konseling dan Psikologi Indonesia, 2026)
Creative problem-solving skills and self-efficacy are crucial competencies that students in the current century must possess to face global challenges and the ever- increasing complexity of information. Self-efficacy, defined as an individual's belief in their ability to complete tasks or achieve goals, is expected to have a strong correlation with optimizing creative thinking skills in finding solutions to problems. Based on this urgency, this correlational quantitative study was conducted with the main objective of empirically testing and analyzing the relationship and influence between self-efficacy variables and creative problem-solving abilities in students. The data collection methods used involved distributing questionnaires to measure self-efficacy based on the dimensions of level, strength, and generality, as well as tests to measure creative problem-solving ability based on the indicators of fluency, flexibility, originality, and elaboration. All instruments were distributed thru the online platform Google Forms. The results of the regression analysis indicate a positive and significant influence of self- efficacy on creative problem-solving ability. This indicates that the stronger the self- efficacy students possess, the higher their creative problem-solving abilities. However, the contribution of self-efficacy to creative problem-solving ability is relatively small, with most of the remaining variation influenced by factors other than self-efficacy.